Faktor-faktor yang mempengaruhi Kualitas Manajer Proyek di Industri Konstruksi: Skill Kepemimpinan, Spesialisasi bidang Pekerjaan dan Aspek Sumber Daya Manusia - Emiyani, Johny; Rusmana, Ganda (Cipta Kind Publisher, 2024)
Previous or relevant research is very important in a research study or scientific article. Previous or relevant research serves to strengthen theories and phenomena related to the relationship or influence between variables. This article reviews the factors influencing the Quality of Project Managers in the Construction Industry, namely Leadership Skills, Job Specialization, and Human Resource Aspects. The purpose of writing this article is to build hypotheses about the influence between variables to be used in future research. The results of this literature review article are: 1) Leadership Skills influence the Quality of Project Managers in the Construction Industry; 2) Job Specialization influences the Quality of Project Managers in the Construction Industry; and 3) Human Resource Aspects influence the Quality of Project Managers in the Construction Industry.